A Conceptual Analysis of Green Human Resource Management, Green Organizational Culture, and Employee Green Behavior towards Environmental Performance - Annisa, Sofina Tri; Abdul Rahim, Ramita; Salleh, Sazimah Mohamed; Zainal, Noor Zalina; Sari, Nor Afni Md (Advances in Social Sciences Research Journal, 2024)
This research addresses a critical gap in the existing literature on green human resource management (GHRM) practices and their influence on a firm's environmental performance. While scholars have demonstrated the positive correlation between GHRM practices and environmental outcomes, there remains a dearth of studies explicating the mediating roles played by green organizational culture and employee green behavior in this relationship. By proposing a comprehensive conceptualization of environmental performance, this study aims to unravel the intricate mechanisms through which GHRM practices exert their impact. The framework introduced not only bridges the existing gap in GHRM literature but also serves as a foundation for understanding the interconnected dynamics between GHRM, green organizational culture, employee behavior, and environmental performance. This conceptual research offers valuable insights that extend beyond theoretical considerations, providing practical implications for fostering sustainable practices, particularly in the context of emerging economies. It aligns economic goals with environmental objectives, thereby contributing to a holistic understanding of the interplay between human resource practices and environmental sustainability.